2014
DOI: 10.11648/j.ajche.20140204.12
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Stereochemistry of the Active Compounds on Fluoride Adsorption Efficiency of the Plant Biomass

Abstract: Several studies have reported various defluoridation capabilities of plant biomasses. The resultant variations in fluoride removal capacities are associated with the presence of different types of active functional groups in the respective biomasses. This study reports of the fluoride removal efficiencies of sisal leaf biomass in comparison. Comparison with other plant biomasses were made and hence the fluoride removal efficiencies of maize leaf (ML), goose grass (GG), banana false stem (BFS), Aloe vera (AV), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…To achieve optimum removal efciency and fuoride ion absorption capacity, neutral pH was chosen as the ideal one. Te results of this investigation are in accordance with the study by Mwakabona et al [41], who found that when pH increased, both removal efciency and adsorption capacity enhanced gradually until an equilibrium point was reached.…”
Section: Efect Of Solution Phsupporting
confidence: 92%
“…To achieve optimum removal efciency and fuoride ion absorption capacity, neutral pH was chosen as the ideal one. Te results of this investigation are in accordance with the study by Mwakabona et al [41], who found that when pH increased, both removal efciency and adsorption capacity enhanced gradually until an equilibrium point was reached.…”
Section: Efect Of Solution Phsupporting
confidence: 92%
“…The hydroxyl functionalities of sisal fibers can interact with hydronium ions in the solution to form positively charged surfaces leading to fluoride uptake. Moreover, other weak van der Waals interactions may occur between fluoride and the sisal surface [ 36 ]. Different scholars have applied cellulose, chitin, and chitosan as adsorption media due to the availability of hydroxyl functionality through H-bonding and other van der Waals interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Biosorption utilizes animal and plant remains in the pulverized form "as is" without prior gasification or charring. A study realized in Tanzania, reported F removal efficiencies, which was 4.1-47.3%, for several biosorbents [134]. In a particular defluoridation study, which was conducted by Yadav et al [135] using three agricultural-based biomasses as adsorbents tested on groundwater containing 5 mg/L F, the authors reported F removal efficacies of 40-58%.…”
Section: Biosorptionmentioning
confidence: 98%
“…Similarly, Aspergillus and Calcium treated Aspergillus biosorbents revealed Fluoride F adsorption capacities of 8.09 mg/g [145]. Differences in the capacity of various biomasses to sequestrate F from water are related to, among other factors, differences in active functional groups in the biomasses [134].…”
Section: Biosorptionmentioning
confidence: 99%